Pilot study for comparative assessment of dual‐energy computed tomography and single‐photon emission computed tomography V/Q scanning for lung perfusion evaluation in infants. Issue 3 (27th December 2021) - Ramirez‐Suarez, Karen I.; Barrera, Christian A.; Otero, Hansel J.; Biko, David M.; States, Lisa J.; Servaes, Sabah; Zhu, Xiaowei; Davis, James C.; Piccione, Joseph; Rapp, Jordan B.
Abstract: Objective: To evaluate clinical applications of dual‐energy computed tomography (DECT) in pediatric‐specific lung diseases and compare ventilation and perfusion findings with those from single‐photon emission computed tomography (SPECT‐CT) V/Q. Methods: All patients at our institution who underwent exams using both techniques within a 3‐month period were included in this study. Two readers independently described findings for DECT, and two other readers independently analyzed the SPECT‐CT V/Q scan data. All findings were compared between readers and disagreements were reassessed and resolved by consensus. Inter‐modality agreements are described throughout this study. Results: Eight patients were included for evaluation. The median age for DECT scanning was 3.5 months (IQR = 2). Five of these patients were scanned for both DECT and SPECT‐CT V/Q studies the same day, and three had a time gap of 7, 65, and 94 days between studies. The most common indications were chronic lung disease (5/8; 63%) and pulmonary hypertension (6/8; 75%). DECT and SPECT‐CT V/Q identified perfusion abnormalities in concordant lobes in most patients (7/8; 88%). In one case, atelectasis limited DECT perfusion assessment. Three patients ultimately underwent lobectomy with corresponding perfusion abnormalities identified by all reviewers on both DECT and SPECT‐CT V/Q in all resected lobes. Conclusion: DECT is a feasible technique that could be considered as an alternative for SPECT‐CT V/Q for lung perfusion evaluation in infants.